Recycling domains in plant cell morphogenesis: small GTPase effectors, plasma membrane signalling and the exocyst - Žárský, Viktor; Potocký, Martin (Biochemical Society transactions, 2010)
The Rho/Rop small GTPase regulatory module is central for initiating exocytotically ACDs (active cortical domains) in plant cell cortex, and a growing array of Rop regulators and effectors are being discovered in plants. Structural membrane phospholipids are important constituents of cells as well as signals, and phospholipid-modifying enzymes are well known effectors of small GTPases. We have shown that PLDs (phospholipases D) and their product, PA (phosphatidic acid), belong to the regulators of the secretory pathway in plants. We have also shown that specific NOXs (NADPH oxidases) producing ROS (reactive oxygen species) are involved in cell growth as exemplified by pollen tubes and root hairs. Most plant cells exhibit several distinct plasma membrane domains (ACDs), established and maintained by endocytosis/exocytosis-driven membrane protein recycling. We proposed recently the concept of a 'recycling domain' (RD), uniting the ACD and the connected endosomal recycling compartment (endosome), as a dynamic spatiotemporal entity. We have described a putative GTPase-effector complex exocyst involved in exocytic vesicle tethering in plants. Owing to the multiplicity of its Exo70 subunits, this complex, along with many RabA GTPases (putative recycling endosome organizers), may belong to core regulators of RD organization in plants.
Keywords: Morphogenesis; morfogeneze; Monomeric GTP-Binding Proteins; exocytóza; Plant Development; Plants; Signal Transduction; Organoids; Models, Biological; stavba rostlin; Cells; vývoj rostlin; signální transdukce; organoidy; Cell Membrane; biologické modely; buňky; rostliny; buněčná membrána; Plant Structures; fyziologie buňky; Cell Physiological Phenomena; monomerní proteiny vázající GTP; Exocytosis